Анализ эффективности деятельности паевых инвестиционных фондов в России - Ногас, И.Л.; Чепорова, Г.Е. (Культура народов Причерноморья, 2014)
В статье рассмотрены общее состояние и основные тенденции развития паевых
инвестиционных фондов (ПИФ), а также управляющих компаний. Проанализированы показатели
доходности ПИФов. Проведена оценка результативности работы самых доходных ПИФов с помощью
показателей соотношения доходности и риска, качества управления, зависимости доходности фонда
от движения финансового рынка и др. У статті розглянуті загальний стан і основні тенденції розвитку пайових інвестиційних
фондів (ПІФ), а також керуючих компаній. Проаналізовано показники прибутковості ПІФ. Проведена
оцінка результативності роботи найдохідніших ПІФ за допомогою показників співвідношення
дохідності та ризику, якості управління, залежності дохідності фонду від руху фінансового ринку та ін. General state and principal development trends of unit funds and managment companies are
considered in the article. The dynamics of development the net asset value, the structure of the investment
portfolio are analyzed. The main element in the construction of unit funds is a management company. Ten most
successful managing companies are singled out in the article, their market situation is considered. The unit
funds rates of return are analyzed. Assessment factors of investment funds work effectiveness such as the Sortino
ratio, the Sharpe ratio, the var ratio, R2 rate, coefficient alpha, beta coefficient are studied. By dint of these
factors, the most profitable funds effectiveness is appraised. The main factors of influence on the unit funds
activity are singled out. Unit funds role and significance in the modern Russian financial market are examined.